Enhanced etch characteristics of EUV PR masked SiON through the ion beam grid pulsing technique - Hae In Kwon; Yun Jong Jang; Kyoung Chan Kim; Hong Seong Gil; Ju Young Kim; Seong Hyun Ryu; Do Seong Pyun; Dae Whan Kim; Woo Chang Park; Ji Yeon Lee; Jin Woo Park; Sang Wuk Park; et al. (Scientific Reports)
Abstract EUV lithography technology, applied in nano-patterning processes, enables the creation of fine patterns below 10 nm. However, issues still remain due to the reduced etch selectivity and increased line edge roughness (LER) caused by the thin thickness and weakness of organic EUV photoresist (PR). In this study, research was conducted to improve the low etch selectivity and high LER using a novel grid pulsed ion beam etching technique. In this system, Ar/H2 plasma is generated in the inductively coupled plasma (ICP) source, and the Ar+/Hx + ion beam is irradiated while fluorocarbon gas is injected into the process chamber. Grid pulsing technique increases the etch selectivity of SiON over EUV PR while improving LER. With a 50% duty ratio and optimal gas flow conditions (Ar:H2 ratio = 1:3 to the ion beam source and CF4:C4F8 = 1:1), the etch selectivity of SiON over EUV PR approached ∞ while maintaining the LER close to the reference.